If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x+4)=4(2x+3)
We move all terms to the left:
2(x+4)-(4(2x+3))=0
We multiply parentheses
2x-(4(2x+3))+8=0
We calculate terms in parentheses: -(4(2x+3)), so:We get rid of parentheses
4(2x+3)
We multiply parentheses
8x+12
Back to the equation:
-(8x+12)
2x-8x-12+8=0
We add all the numbers together, and all the variables
-6x-4=0
We move all terms containing x to the left, all other terms to the right
-6x=4
x=4/-6
x=-2/3
| 55=11t | | -2(x+4)=4(2x-3) | | 44=37+u | | 1/5x2/3x-2=-2/5x | | -1+5=2x | | -2(,4)=4(2x-3) | | 5+5(4+7r)=95 | | (3(3x-9))/4=86 | | 5x+2-x+10=4x+12 | | 2^(5x+4)=6 | | 25=-4x+12 | | 8m-40=4(4m=20) | | 142+56=28w | | -6x=954 | | 9-3x+x=6x | | 4(2x+1)+3x=24 | | 9+3x+x=6x | | 2n4⋅6=n4 | | 78=12y | | 9x+3x+x=6x | | 7x=3-2x-5=20 | | 3πx=-15π | | 17-5r+9r=-12r+6-1 | | 1760+230.25x=4292.75 | | 3(2x-7)=6x-7 | | 5(y-2)=-8y+42 | | -13b-39=11b-37 | | 17-5r+9=-12r+6-1 | | 9w+4=-16+9w | | |-2b|=12 | | -5x=-670 | | 7m+3(-8m+1)=105 |